2017
DOI: 10.1002/ldr.2867
|View full text |Cite
|
Sign up to set email alerts
|

Effects of land preparation and plantings of vegetation on soil moisture in a hilly loess catchment in China

Abstract: In the dryland and degraded regions, soil moisture is the primary factor determining ecological restoration. Proper land preparations and vegetation restoration can improve soil moisture and benefit land restoration. Identifying their effects on soil moisture is thus essential for developing suitable management strategies. In this study, four typical land preparation techniques (level ditches, fish‐scale pits, zig terraces, and level benches) and non‐native vegetation types (Prunus armeniaca, Platycladus orien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 72 publications
(123 reference statements)
0
29
0
Order By: Relevance
“…Literature provides ample evidences regarding the efforts which are being made to improve the productivity of degraded lands [5][6][7][8]. Many national and international agencies are working on the improvement of such land types [9][10][11] including land degradation neutrality (LDN) and land restoration for attaining UN-SDGs [12][13][14]. According to UNCCD, LDN is a situation where there is no further degradation to the land system while enhancing the vitality, productivity and ecosystem services of the land system for meeting the food and nutritional demand of the current and future generations, and also for attaining ecosystem sustainability (www.unccd.int).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature provides ample evidences regarding the efforts which are being made to improve the productivity of degraded lands [5][6][7][8]. Many national and international agencies are working on the improvement of such land types [9][10][11] including land degradation neutrality (LDN) and land restoration for attaining UN-SDGs [12][13][14]. According to UNCCD, LDN is a situation where there is no further degradation to the land system while enhancing the vitality, productivity and ecosystem services of the land system for meeting the food and nutritional demand of the current and future generations, and also for attaining ecosystem sustainability (www.unccd.int).…”
Section: Introductionmentioning
confidence: 99%
“…The Global Partnership on Forest and Landscape Restoration (GPFLR) is another enterprise operational at global level for both financing and practising the restoration initiatives across the globe [11]. Furthermore, Keesstra et al [12] suggested four inventive methods to attain LDN and developing suitable remediation techniques for addressing soil-related SDGs, whereas Tianjiao et al [13] reported the effect of various land management practices and Novara et al [14] studied the effect of sustainable farming on soil carbon recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent researches have turned to soil moisture, evapotranspiration and other hydrological variables as a complement for parameter calibration [5][6][7][8][9][10][11][12][13][14]. Among different surface/subsurface components, soil moisture plays a significant role in the energy and water balance of the hydrologic cycle [15][16][17][18]. Especially in a heavy rainfall event where the amount of precipitation is close to the storage capacity of the unsaturated zone, current soil moisture content has a tremendous influence on whether surface flow would occur [19].…”
Section: Introductionmentioning
confidence: 99%
“…• Diversion hole is a better measure to improve rainfall resource utilization, especially under high rainfall events. the surface runoff during heavy hard rain by intercepting rainwater on the soil surface to the pit and increasing water infiltration (Fu et al 2010;Feng et al 2018). However, fish-scale pit also increased the ineffective evaporation because of the large contact area between soil and air (Li et al 2011).…”
Section: Introductionmentioning
confidence: 99%